Differences in Accessibility of Public Health Facilities in Hierarchical Municipalities and the Spatial Pattern Characteristics of Their Services in Doumen District, China - Dahao Zhang; Guojun Zhang; Chunshan Zhou (Land, 2021)
This study used the two-step floating catchment area method and potential model to calculate facility accessibility and potential service scope of public health infrastructure distribution, and to evaluate its spatial equity. We applied the Gini coefficient to measure the spatial equilibrium at each level of public health infrastructure in Doumen District, Guangdong, China, from different perspectives. The following results were obtained: (1) Significant spatial differences were observed in the accessibility of public health facilities among different levels; the higher the health facility level, the greater the difference in spatial accessibility. Spatial differences in the accessibility of public health infrastructure at the primary level and higher were distributed in a block-like pattern, while spatial differences in the accessibility of rural health stations were distributed in a circular pattern. Administrative villages tended to have the highest and lowest accessibility of tertiary and secondary hospitals, but not of primary hospitals and rural health stations. The frequencies for administrative villages with the highest and lowest accessibility were 32.8% and 49.6% of the total number of villages in the district, respectively, for tertiary hospitals; 39.2% and 48.8% for secondary hospitals; 19.2% and 24.8% for primary hospitals; 16.8% and 21.6% for rural health stations. (2) The potential service scope was spatially dissociative for tertiary hospitals, and differed more significantly in terms of space for secondary hospitals; the potential service scope of the two overlapped. The potential service scope of primary hospitals was relatively balanced, with strong spatial continuity, while that of rural health service centers was spatially fragmented. The service scope of rural health service centers was mostly consistent with their respective village-level administrative divisions. (3) The higher the level of public health infrastructure, the less balanced its spatial layout. Conversely, the lower the level of public health infrastructure, the more balanced its spatial layout.